1/f noise in MgO double-barrier magnetic tunnel junctions - COEY, JOHN MICHAEL DAVID (My University, 2011)
Low frequency noise has been investigated in MgO double-barrier magnetic tunnel junctions (DMTJs) with tunneling magnetoresistance (TMR) ratios up to 250% at room temperature. The noise shows a 1/f frequency spectrum and the minimum of the noise magnitude parameter is 1.2 x 10(-10) mu m(2) in the parallel state for DMTJs annealed at 375 degrees C. The bias dependence of noise and TMR suggests that DMTJs with MgO barriers can be useful for magnetic field sensor applications.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; MAGNETORESISTANCE